Aneurysm Development in Patients With a Bicuspid Aortic Valve Is Not Associated With Transforming Growth Factor-β Activation. Issue 4 (April 2015) - Paloschi, Valentina; Gådin, Jesper R.; Khan, Shaukat; Björck, Hanna M.; Du, Lei; Maleki, Shohreh; Roy, Joy; Lindeman, Jan H.M.; Mohamed, Salah A.; Tsuda, Takeshi; Franco-Cereceda, Anders; Eriksson, Per
Abstract : Objective—: Patients with bicuspid aortic valve (BAV) have an increased risk of developing ascending aortic aneurysms. Transforming growth factor-β (TGFβ) is a crucial factor of vascular remodeling, the impaired signaling of which can alter the structure and composition of the extracellular matrix. In this study, we analyzed the activity of TGFβ in aneurysmal and nonaneurysmal ascending aorta from BAV patients, using tricuspid aortic valve (TAV) patients as a reference group. Approach and Results—: The response to exogenous TGFβ was analyzed with regard to gene expression in primary aortic smooth muscle cells that were isolated from 7 BAV and 5 TAV patients and in valve fibroblasts from 7 BAV and 8 TAV patients. The set of genes that were significantly changed by TGFβ (217 genes) was compared with gene expression profiles of the ascending aorta from BAV and TAV patients (139 arrays). By principle component analysis, based on the 217 genes, gene expression differed significantly in the intima/media region between aneurysmal BAV and TAV aortas, driven by the response in TAV patients. During aneurysm development the levels of phosphorylated SMADs and the availability of free TGFβ were lower in BAV patients compared with TAV. Confocal microscopy analysis showed a higher colocalization of latency associated peptide and latent TGFβ binding protein 3 in BAV aortas. Conclusions—: Our findings suggest that TGFβ activation during aneurysm formation is muted in patients with BAV, possibly as a result of an increased TGFβ sequestration in the extracellular space. Abstract : Supplemental Digital Content is available in the text.